Challenges towards Revitalizing Hemp: A Multifaceted Crop. (November 2017) - Schluttenhofer, Craig; Yuan, Ling
Abstract : Hemp has been an important crop throughout human history for food, fiber, and medicine. Despite significant progress made by the international research community, the basic biology of hemp plants remains insufficiently understood. Clear objectives are needed to guide future research. As a semi-domesticated plant, hemp has many desirable traits that require improvement, including eliminating seed shattering, enhancing the quantity and quality of stem fiber, and increasing the accumulation of phytocannabinoids. Methods to manipulate the sex of hemp plants will also be important for optimizing yields of seed, fiber, and cannabinoids. Currently, research into trait improvement is hindered by the lack of molecular techniques adapted to hemp. Here we review how addressing these limitations will help advance our knowledge of plant biology and enable us to fully domesticate and maximize the agronomic potential of this promising crop. Trends: For states which define hemp (<0.3% THC) as distinct from marijuana, the USA Agriculture Act of 2014 allows departments of agriculture or universities to cultivate hemp as part of a research pilot program. As of 2017, at least 39 US universities and dozens of researchers have begun studying hemp, yet guidance on top research priorities are lacking. While traditionally a fiber and grain crop, hemp has emerged as a source of nonhallucinogenic medicinal phytocannabinoids (e.g., CBD) with distinct properties from marijuana. Dozens of clinical studies are now investigating anecdotal uses of CBD to treat various medical conditions. The last several years have seen advancements in understanding Cannabis genetics through publications of a draft genome, transcriptome sequencing, quantitative trait mapping, and genetic comparisons between hemp and marijuana.